La Conversation des sexes: philosophie du consentement - Garcia, Manon (Climats, 2021)
« L'affaire Weinstein et le mouvement #MeToo ont mis la question des violences sexuelles au premier plan. Depuis, le consentement renvoie naturellement au consentement sexuel et amoureux, envisagé comme un sésame de l'égalité entre femmes et hommes. Pourtant, il est bien difficile à définir, et soulève trois problèmes. Le problème juridique, bien connu de celles et ceux qui suivent l'actualité, peut être résumé ainsi : que faire pour que les cas de viol, d'agression et de harcèlement sexuels soient efficacement punis? Le deuxième problème est moral : comment penser des relations amoureuses et sexuelles qui ne soient pas fondées sur des normes sociales sexistes et inégalitaires? Enfin, le problème politique : comment ne pas reconduire les injustices de genre qui se manifestent dans les rapports amoureux et sexuels? La magistrale analyse du consentement que propose Manon Garcia revisite notre héritage philosophique, plongeant au cœur de la tradition libérale, mettant à nu ses impensés et ses limites. De John Locke aux théoriciennes féministes françaises et américaines, en passant par Michel Foucault et les débats sur la pratique du BDSM, c'est une nouvelle cartographie politique de nos vies privées que dessine cet essai novateur. Au terme de ce livre, il s'agira en somme, pour reprendre la formule de Gloria Steinem, d'« érotiser l'égalité » plutôt que la domination : en ce sens, le consentement sexuel, conçu comme conversation érotique, est sans doute l'avenir de l'amour et du sexe. »
Keywords: 2000 à aujourd'hui; approches et analyses; consentement; cours; discipline; droits des femmes*; europe; france; féminisme pop; justice sociale; metoo; phi4336; philosophie; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; thématiques

Féminismes et pop culture - Padjemi, Jennifer (Points (Paris); 5721; P5721, 2021)
"Dans un essai passionné et engagé, Jennifer Padjemi explore l'alliance, pour le meilleur et pour le pire, des féminismes et de la pop culture. A partir des mouvements féministes modernes, elle décortique le rapport que nous entretenons avec les objets culturels les plus populaires. En utilisant la pop culture comme un miroir de notre société mondialisée, l'auteure interroge les liens d'interdépendance entre consommation de masse et idéologie progressiste, et jette un regard joyeux et lucide sur nos divertissements, sans concession au patriarcat."--Quatrième de couverture.
Keywords: afro-féminisme; approches et analyses; care; communication; corps; cours; discipline; féminisme afropéen; féminisme pop; féminismes noirs; intersectionnalité; journalisme; premier cycle; sex2283; sexualité; thématiques; écriture des femmes*; études culturelles

Navigating, challenging, and contesting normative gendered discourses surrounding women’s pornography use - Marques, Olga (Journal of Gender Studies, 2019)
While there exists some empirical research on women’s use of pornography, the manner in which women do, and how they understand their pornographic spectatorship, remains under-examined. Focusing on the narratives of 26 women gained through both focus groups and individual interviews, this research explores how women who use pornography and other sexually explicit materials navigate, reaffirm, challenge, and contest normative gendered boundaries that surround women’s sexuality, sexual pleasure, and women’s pornographic use. While ‘pornography as female degradation’ is the most visible feminist discourse, the findings of this study suggest that the meanings attributed to both the experience of engaging with pornography, as well as with pornographic materials themselves, were far from wholly degrading, and in fact, served to provide pleasure, sexual self-actualization, and even corporeal validation – disrupting normative discourses of desiring and desirable bodies.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; corps; cours; féminisme pop; ontario; premier cycle; périodes historiques; régions géographiques; sex1911; sexualité; thématiques

Pornography, feminist views of - Davis, Berta (The International Encyclopedia of Human Sexuality, 2015)
Feminist women's attitudes toward pornography are significantly polarized. Anti‐porn feminists have taken a position that pornography is degrading toward women, leads to distortion of healthy male‐female sexuality, leads to distorted images of the female body, increases male anxiety about sexual adequacy, sexual compulsivity, and increase violence toward women including rape and sexual harassment.
Keywords: approches et analyses; cours; discipline; féminisme anti-porn; féminisme pop; pornography; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; thématiques

The mask you live in - Newsom, Jennifer Siebel; Anthony, Jessica; Kanopy (Firme) (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, attitudes performatives, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France); Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Collection Nouvelles scènes, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

Rethinking the effects paradigm in porn studies - McNair, Brian (Porn Studies, 2014)
It has been an assumption of most anti-pornography discourse that porn damages women (and children) in a variety of ways. In Porno? Chic!, the author interrogated this assumption by examining the correlation between the incidence of sexual violence and other indicators of misogyny, and the availability and accessibility of pornography within a number of societies. This article develops that work with a specific focus on the regulatory environment as it relates to pornography and sexual representation. Does a liberal regulatory regime in sexual culture correlate with a relatively advanced state of sexual politics in a given country? Conversely, does an illiberal regime, where pornography and other forms of sexual culture are banned or severely restricted, correlate with relatively strong patriarchal structures? A comparative cross-country analysis seeks to explain the correlations identified, and to assess the extent to which the availability of porn can be viewed as a causal or a consequential characteristic of those societies where feminism has achieved significant advances.
Keywords: LGBTQIA2+; analyse comparée; approches et analyses; communication; corps; cours; discipline; droits des femmes*; féminisme pop; histoire et politique; identités LGBTQIA2+; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; violences; études culturelles

The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Next wave : new directions in women's studies, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles

Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles

The feminist porn book: the politics of producing pleasure - Taormino, Tristan; Shimizu, Celine Parreñas; Penley, Constance; Miller-Young, Mireille (The Feminist Press at the City University of New York, 2013)
''This book brings together writings by feminists in the adult industry and research by feminist porn scholars. It investigates not only how feminists understand pornography, but also how feminists do porn - that is, direct, act in, produce, and consume this kind of 'industry'. With contributions by Susie Bright, Candida Royalle, Betty Dodson, Nina Hartley, Buck Angel, Lynn Comella, Jane Ward, Ariane Cruz, Kevin Heffernan, and more.''-- Fourni par l'éditeur.
Keywords: approches et analyses; arts; arts visuels et médiatiques; cinéma; communication; corps; cours; discipline; féminisme pop; féminisme pro-sexe; histoire et politique; premier cycle; ressource en ligne; sciences humaines; sex1911; sex1920; sexologie; sexualité; thématiques

Féminismes et pornographie - Courbet, David (L'attrape-corps, 2012)
Comment le féminisme peut se reconnaître dans la pornographie Objet de débats où la passion l'emporte bien souvent sur la raison, la pornographie semble à première vue s'opposer au féminisme. Or, les années 1980 voient éclore aux Etats-Unis un courant se définissant comme " pro-sexe " porté par des figures telles Annie Sprinkle ou Candida Royalle. Avec l'idée que la pornographie n'est pas systématiquement condamnable, la question suivante s'impose : peut-on parler de moyen d'émancipation ? La femme doit être libre de choisir la sexualité qui lui convient. Les films pornographiques conçus par des hommes et pour des hommes ne lui permettant pas d'obtenir une satisfaction complète, des réalisatrices, parmi lesquelles Erika Lust, Ovidie ou Emilie Jouvet, promeuvent une pornographie alternative où le plaisir féminin est - enfin - mis en exergue. Et brisent les standards pornographiques dominants ! Peu étudiées en France, les thèses défendues par les féministes pro-sexe n'ont encore que peu d'échos au sein du grand public. Basé notamment sur une dizaine d'entretiens de spécialistes et professionnels, ce travail cherche à élucider en quoi le féminisme peut se reconnaître dans la pornographie. Et inversement.
Keywords: approches et analyses; corps; cours; discipline; féminisme pop; féminisme pro-sexe; journalisme; premier cycle; science politique; science politique et droit; sciences humaines; sex1911; sexologie; sexualité; thématiques; travail

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Anti-porn: the resurgence of anti-pornography feminism - Long, Julia (Zed Books, 2012)
"Anti-porn feminism is back. Countering the ongoing 'pornification' of Western culture and society, with lads' mags on the middle shelf and lap-dancing clubs in residential areas, anti-porn movements are re-emerging among a new generation of feminist activists worldwide. This essential new guide to the problems with porn starts with a history of modern pro and anti political stances before examining the ways in which the new arguments and campaigns around pornography are articulated, deployed and received. Drawing on original ethnographic research, it provides an in-depth analysis of the groups campaigning against the pornography industry today, as well as some eye-opening facts about the damage porn can do to women and society as a whole. This unique and inspiring book explains the powerful comeback of anti-porn feminism, and it controversially challenges liberal perspectives and the mainstreaming of a porn culture that threatens to change the very nature of our intimate relationships"--Résumé de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme anti-porn; féminisme pop; militance; patriarcat; premier cycle; sex1911; sexualité; systèmes d'oppressions; thématiques

Miss representation - Siebel Newsom, Jennifer; Dietrich, Claire; Costanzo, Julie; Congdon, Jessica; Roco Films Educational (Firme); Girls Club Entertainment (Girls Club Entertainment, 2011)
Like drawing back a curtain to let bright light stream in, MISS REPRESENTATION uncovers a glaring reality we live with every day but fail to see. Written and directed by Jennifer Siebel Newsom, the film exposes how mainstream media contributes to the under-representation of women in positions of power and influence in America. The film challenges the media’s limited and often disparaging portrayals of women and girls, which make it difficult for women to achieve leadership positions and for the average woman to feel powerful herself. In a society where media is the most persuasive force shaping cultural norms, the collective message that our young women and men overwhelmingly receive is that a woman’s value and power lie in her youth, beauty, and sexuality, and not in her capacity as a leader. While women have made great strides in leadership over the past few decades, the United States is still 90th in the world for women in national legislatures, women hold only 3% of clout positions in mainstream media, and 65% of women and girls have disordered eating behaviors.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; documentaire; féminisme pop; premier cycle; périodes historiques; représentation des femme*; régions géographiques; santé; sex2283; sexualité; thématiques; travail; états-unis

La transidentité: de l'espace médiatique à l'espace public - Espineira, Karine (Champs visuels, 2008)
C'est à partir de l'opération de Christine Jorgensen en 1952 au Danemark, que le fait qu'un homme puisse devenir une femme, après une intervention chirurgicale, entre dans l'esprit du grand public en raison de sa très forte médiatisation. Les identités trans' sont alors loin de s'affirmer comme telles. Il faudra attendre la fin des années 80 pour assister à l'émergence d'une visibilité prenant une forme revendicative. Entre les deux, la psychiatrisation de l'identité. Grâce à l'Internet, les transidentités ne sont plus isolées les unes des autres et ne rejouent plus la dramatique du changement de sexe comme une individuelle et éternelle première fois. Une mémoire s'élabore, se fixe et génère une culture. Leurs relations à l'information et l'identitaire questionnent tout autant. Cette recherche considère le groupe transidentitaire comme un monde social s'institutionnalisant dans un esprit multidisciplinaire à la lumière des sciences de l'information et de la communication, de la psychosociologie, de la théorie de l'engagement, de l'ethnométhodologie, de la sociologie de la traduction et de la communication instituante. L'analyse du traitement télévisuel de la transidentité, considérée comme expression la plus singulière de l'identité, est-elle susceptible de donner des outils de lectures sur la construction des normes de genre au-delà de la transidentité ?
Keywords: 1900-1999; 1950-1959; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; danemark; discipline; discours dominant; europe; féminisme pop; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; transféminisme

Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

The trouble with nature: sex in science and popular culture - Lancaster, Roger N. (University of California Press, 2003)
Roger N. Lancaster provides the definitive rebuttal of evolutionary just-so stories about men, women, and the nature of desire in this spirited expose of the heterosexual fables that pervade popular culture, from prime-time sitcoms to scientific theories about the so-called gay gene.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme pop; genre; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; soc2014; thématiques; études culturelles

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Sexy bodies: the strange carnalities of feminism - Grosz, E. A.; Probyn, Elspeth (Routledge, 1995)
Are bodies sexy? How? In what sorts of ways? Sexy Bodies investigates the production of sexual bodies and sexual practices, of sexualities which are dyke, bi, transracial, and even hetero. It celebrates lesbian and queer sexualities but also explores what runs underneath and within all sexualities, discovering what is fundamentally weird and strange about all bodies, all carnalities. Looking at a pleasurable variety of cultural forms and texts, the contributors consider the particular charms of girls and horses, from National Velvet to Marnie; discuss figures of the lesbian body from vampires to tribades to tomboys; uncover 'virtual' lesbians in the fiction of Jeanette Winterson; track desire in the music of legendary Blues singers; and investigate the ever-scrutinised and celebrated body of Elizabeth Taylor. The collection includes two important pieces of fiction by Mary Fallon and Nicole Brossard. Sexy Bodies makes new connections between and amongst bodies, cruising the borders of the obscene, the pleasurable, the desirable and the hitherto unspoken rethinking sexuality anew as deeply and strangely sexy.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; féminisme pop; identités LGBTQIA2+; lesbianisme; lit4700; premier cycle; queer; ressource en ligne; sexualité; thématiques

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis